2015
DOI: 10.3844/ajassp.2015.506.515
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Satellite Images to Reconstruct Recent Evolution of Domitian Coastline

Abstract: In the last decades, combinations of natural and human factors\ud have resulted in extensive morphological changes to our coastlines and in\ud many cases have amplified erosion. In order to limit these changes and their\ud impact on coastal zone, it is important to plan specific actions; for this\ud purpose detailed cognizance of coastal zone is necessary. Different and\ud heterogeneous data such as historical and recent maps, remotely sensed\ud images and topographic survey result very useful to reconstruct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…and MIR (middle infrared) band (Wang et al, 2018). The specific application to the single spectra of the indexes described may vary depending on the images used (Maglione et al, 2015); for the Sentinel images used in this experiment it is reported in more detail below under the specific paragraph 2.3. MNDWI index produces three results: (i) water will have greater positive values than in the NDWI as it absorbs more MIR light than NIR light; (ii) built-up land will have negative values as mentioned above; and (iii) soil and vegetation will still have negative values as soil reflects MIR light more than NIR light and the vegetation reflects MIR light still more than green light (Jakovljević et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and MIR (middle infrared) band (Wang et al, 2018). The specific application to the single spectra of the indexes described may vary depending on the images used (Maglione et al, 2015); for the Sentinel images used in this experiment it is reported in more detail below under the specific paragraph 2.3. MNDWI index produces three results: (i) water will have greater positive values than in the NDWI as it absorbs more MIR light than NIR light; (ii) built-up land will have negative values as mentioned above; and (iii) soil and vegetation will still have negative values as soil reflects MIR light more than NIR light and the vegetation reflects MIR light still more than green light (Jakovljević et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The rocky parts are less sensitive to instantaneous dynamic change than the sandy ones. The index I was also considered to evaluate the average shift between two temporal consecutive shorelines [11]. They compared shorelines during 2005 and 2011 and they evidenced that the effects of the human intervention, like the installation of breakwaters, limit erosion phenomena near shore zone.…”
Section: Vhr Optical Hr Sarmentioning
confidence: 99%
“…Several survey methodologies are used for the detection of shorelines: from traditional topographical and GNSS (Global Navigation Satellite System) surveys to remote sensing techniques (aerial and unmanned aerial vehicle (UAV) photogrammetry, video systems and satellite optical and SAR images [8,9]), as widely discussed in another recent work [10]. In the last few years, the use of optical and SAR satellite images for automatic and semi-automatic shoreline extraction has complemented the traditional approach based on surveying methods and air-photo processing [11]. Several approaches have been proposed to outline the shoreline using remote sensing, such as edge detection, segmentation and classification approaches [6].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the previous paragraph, different types of remote sensing data have been used in coastal environment applications. High resolution satellite data and air photos were used to monitor the coastline's changes or to measure volume changes in coastal areas [18][19][20][21], sea surface temperatures [22,23], sea ice coverage [24,25], and coastal change processes [26,27]. A review paper summarizing the remote processing methods performed in shoreline delineation has been presented [28].…”
Section: Introductionmentioning
confidence: 99%